THE EFFECTIVENESS OF USING LEARNING JOURNAL ON EIGHT GRADE STUDENTS’ WRITING ABILITY IN WRITING RECOUNT TEXT (RETAIN, 2017)
THE EFFECTIVENESS OF USING LEARNING JOURNAL ON EIGHT GRADE STUDENTS’ WRITING ABILITY IN WRITING RECOUNT TEXT Ananda Rival Prakoso English Department Faculty, Faculty of Languages and Arts, State University rivalus.tapiosman@gmail.com Abstrak Menulis adalah salah satu keterampilan produktif dalam belajar bahasa Inggris. Ada berbagai macam strategi untuk meningkatkan kemampuan menulis. Salah satunya adalah dengan menulis jurnal pembelajaran untuk mengingat kembali perkembangan dan perasaan dalam pembelejaran siswa di kelas.Oleh karena itu, penelitian ini dilakukan untuk mengetahui apakah penggunaan jurnalpembelajaran efektif untuk meningkatan kemampuan menulis siswa dalam menulis teks recount. Model penelitian yang digunakan adalah penelitian berbasis eksperimen. Fokus dalam penelitian ini dibatasi menjadi komponen tulisan siswa dan jurnal pembelajaran. Dua kelas delapan dipilih menjadi subjek penelitian ini. Pre-test dan post-test digunakan untuk mengambil data komponen tulisan siswa-siswa. Sebagai tambahan, grup eksperimen diberikan treatmen menulis jurnal pembelajaran. Hasil dari penelitian yang dilakukan menunjukan bahwa ada perbedaan signifikan antara grup eksperimen dan kontrol dimana grup eksperimen memperoleh skor menulis lebih tinggi dari grup kontrol. Selain itu,hasilnya juga menunjukkan bahwa jurnal pembelajaran memiliki efek moderat dalam meningkatkan skor komponen tulisan siswa Kata kunci: Jurnal pembelajaran, komponen-komponen tulisan, keefektifan. Abstract Writing is one productive skill in learning English. There are many strategies to improve writing ability. One of them is by writing learning journal to recall the progress that has been achieved through the class. Learning journal is a kind of journal that contains students’ progress and feeling about their learning in the class. Therefore, this study is conducted to find out whether the use of learning journal is effective to improve students’ writing ability in writing recount text. Experimental research was chosen as the research design. The focus is limited into students writing components and learning journal content. Two classes of eight grader students were the participants in this research. Pre-test and post-test were administered to collect the data of students’ writing components. Moreover, experimental group were given the treatment of writing learning journal. The results found that there are significance difference between experimental and control group where experimental has higher score of writing ability. It is also found that learning journal were moderate effective in improving students’ writing components score. Keywords: Learning journal, Writing components, Effectiveness.